Cardioprotective effects of native herb-derived cardiac tonic on infarct size in a mouse model of experimental myocardial infarction (Asian-Australasian Journal of Bioscience and Biotechnology, 2024)
Cardiac remodeling is a significant issue involving molecular, cellular, and interstitial changes that affect the size, mass, integrity, and function of the heart following a myocardial infarction (MI). We hypothesized that therapy with mixed herbal extracts has a protective effect in mouse models of MI. The underlying mechanisms are thought to be protective against left ventricular (LV) remodeling through reduced collagen deposition. We therefore studied the effects of mixed herbal extracts commonly used in various ways in the belief that they have beneficial effects on cardiac disease. MI was induced by left anterior descending (LAD) coronary artery ligation in switch albino mice. Ethanol extracts of herbs Arjuna bark, oleander leaves, ginseng root, garlic, cardamom seeds and oregano leaves were prepared by ethanol extraction and rotary evaporation technique of dried herbs and then mixed the extracts to make a therapeutic cocktail. The mixture is then administered orally by lavage for 28 days. At the end of 28 days cardiac tissues were harvested and stored for histopathology analysis and assessment of SOD levels. Survival curve data over a period of 28 days showed significant (P